Effect of Neonatal Exposure to AED on Synaptic Maturation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Pharmacologists at Georgetown University, Washington, DC examined functional synaptic maturation in striatal medium spiny neurons from neonatal rats exposed to antiepileptic drugs (AED) with proapoptotic action (phenobarbital, phenytoin, lamotrigine) and without proapoptotic action (levetiracetam).